Promoting technical literature in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
There is a common belief that Africans are more accustomed to reaming by word of mouth than by the written word: but a recent survey commissioned by CTA, the French Ministry of Cooperation and ACCT challenges this view. In fact, the authors of the...